2017
DOI: 10.3892/mmr.2017.8141
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer effects of Cucurbitacin I inhibited cell growth of human non‑small cell lung cancer through PI3K/AKT/p70S6K pathway

Abstract: The present study aimed to identify potential anticancer effects of Cucurbitacin I regulators on cell growth of human non‑small cell lung cancer (NSCLC) and to explore their mechanism. The results indicated that the anticancer effects of Cucurbitacin I markedly attenuated cell proliferation, and induced apoptosis in NSCLC. Furthermore, Cucurbitacin I suppressed phosphatidylinositol‑4,5‑bisphosphate 3‑kinase (PI3K), phosphorylation (p)‑AKT and p‑p70S6K pathway in NSCLC. Then, (PI3K) inhibitor increased anticanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…at present, in addition to surgery, the development of antitumor drugs is also very important. cucurbitacin i has a strong antitumor activity (6,7). cucurbitacin i has been reported to induce death in various types of tumor cells; for example it can induce apoptosis in non-small cell lung cancer cells and osteosarcoma cells by inhibiting the Pi3K/aKT/p70S6K and STaT3 signaling, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…at present, in addition to surgery, the development of antitumor drugs is also very important. cucurbitacin i has a strong antitumor activity (6,7). cucurbitacin i has been reported to induce death in various types of tumor cells; for example it can induce apoptosis in non-small cell lung cancer cells and osteosarcoma cells by inhibiting the Pi3K/aKT/p70S6K and STaT3 signaling, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent findings, cucurbitacin i, which is 1 of 12 variants of cucurbitacins, has demonstrated a potent anticancer effect on non-small cell lung cancer cells (6). cucurbitacin i has been reported to cause cancer cell death by inhibiting multiple signaling pathways, such as the Janus kinase (JaK)/STaT3, Pi3K/aKT/p70S6K and serine/threonine-protein kinase PaK1 (PaK1)/PaK4 pathways (7)(8)(9). However, the underlying mechanism for the anticancer effect of cucurbitacin i is not yet completely understood, and further studies are required to clarify it.…”
Section: Introductionmentioning
confidence: 99%
“…It also displays anticancer (Ganesan and Xu, 2017;He et al, 2016), insulinotropic (Folador et al, 2010) and α-glucosidase-inhibiting activity (Choo et al, 2012). Cucurbitacins B, E, I, at prolonged treatment, are all cytotoxic, inhibit STAT3 (Chan et al, 2010;Liu et al, 2020;Oi et al, 2016;Seo et al, 2014), disrupt cytoskeleton organization (Knecht et al, 2010;Sari-Hassoun et al, 2016;Yin et al, 2008), inhibit PKB phosphorylation (Si et al, 2019;Zhou et al, 2017;Zhu et al, 2018), and are particularly studied for their anti-microbial (Hussain et al, 2014) and anti-cancer effects (Garg et al, 2018;Li et al, 2018;Si et al, 2019). Cucurbitacin B was also found to display insulinotropic activity .…”
Section: Discussionmentioning
confidence: 99%
“…As one of the 12 categories of cucurbitacins, cucurbitacin I, a selective inhibitor of JAK2/STAT3, has a potent anticancer effect on several types of cancer cells, including breast cancer, lung cancer, and glioma, which is comparable to cucurbitacin B and D, both of them suppress the proliferation of a variety of cancer cells in vitro and vivo . The inhibition of JAK/STAT3, PI3K/Akt/p70S6K, or PAK1/PAK4 signaling pathways, were recognized to be involved in the anti‐cancer action of cucurbitacin I. Zhang et al further confirmed that cucurbitacin I induced strong autophagy and autophagic death in cancer cells. In fact, the molecular and cellular mechanisms involved in the induction of cucurbitacin‐I in cancer cell death are very complex, which deserves further study to improve cancer chemotherapy, and reduce potential resistance.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 As one of the 12 categories of cucurbitacins, cucurbitacin I, a selective inhibitor of JAK2/STAT3, has a potent anticancer effect on several types of cancer cells, including breast cancer, lung cancer, and glioma, which is comparable to cucurbitacin B and D, both of them suppress the proliferation of a variety of cancer cells in vitro and vivo. 8,9 The inhibition of JAK/ STAT3, 10 PI3K/Akt/p70S6K, 11 or PAK1/PAK4 signaling pathways, 12 were recognized to be involved in the anti-cancer Yinyun Ni and Sisi Wu contributed equally to this work and should be considered co-first authors. action of cucurbitacin I. Zhang et al 13 further confirmed that cucurbitacin I induced strong autophagy and autophagic death in cancer cells.…”
Section: Introductionmentioning
confidence: 99%